Effect of Head Position on Facial Soft Tissue Depth Measurements Obtained Using Computed Tomography1. Issue 1 (18th August 2015) - Caple, Jodi M.; Stephan, Carl N.; Gregory, Laura S.; MacGregor, Donna M.
Abstract: Facial soft tissue depth (FSTD) studies employing clinical computed tomography (CT) data frequently rely on depth measurements from raw 2D orthoslices. However, the position of each patient's head was not standardized in this method, potentially decreasing measurement reliability and accuracy. This study measured FSTDs along the original orthoslice plane and compared these measurements to those standardized by the Frankfurt horizontal (FH). Subadult cranial CT scans ( n  = 115) were used to measure FSTDs at 18 landmarks. Significant differences were observed between the methods at eight of these landmarks ( p  <   0.05), demonstrating that high‐quality data are not generated simply by employing modern imaging modalities such as CT. Proper technique is crucial to useful results, and maintaining control over head position during FSTD data collection is important. This is easily and most readily achieved in CT techniques by rotating the head to the FH plane after constructing a 3D rendering of the data.